Performance analysis of microfluidic fuel cells with various inlet locations and multiple compartments. (15th June 2018) - Tanveer, Muhammad; Kim, Kwang-Yong
Highlights: Modifications of a membraneless microfluidic fuel cell were proposed and evaluated. With inlets at channel center, current density increased by 3-fold compared to Y-channel. Multiple oxidant streams increased current density by 10 hold compared to single stream. Multiple compartments increased current density by 3 hold compared to single channel. Abstract: Computational evaluation of three design modifications of a membraneless microfluidic fuel cell (MMFC), i.e., inlets located midway along the microchannel, multiple compartments in the channel cross section, and a multi-stream (oxidant-fuel-oxidant) configuration, is performed in this work. The first two modifications are novel concepts proposed in this work. These adjustments to the microchannel are introduced to decrease the negative effects caused by the increased channel length, width, and height on the performance of MMFCs. Formic acid and oxygen are dissolved in sulfuric acid solution as the fuel and oxidant, respectively. Simulations are executed by employing three-dimensional Navier-Stokes equations and mass transport equation for the analyses of flow and species concentration. The electro-chemical reaction is modeled using Butler-Volmer equations. Based on the study that investigated the inlet location, inlets placed at the center of the microchannel are shown to be the best option among the selected inlet positions. Additionally, the multi-compartment configuration enhances the current density by as much as three times compared to a simple square microchannel.